The Influence of Memorable Tourism Experiences, Destination Image, and Tourist Attractions on Loyalty in Natural Tourism at Lake Ranau, South OKU Regency, through Tourist Satisfaction - Ulfa Shabrina; Sulastri; Muchsin Saggaf Shibab (Dinasti Publisher, 2024)
The aim of this study is to demonstrate and analyze the relationships between memorable tourism experiences, destination image, tourist attractions, loyalty, and satisfaction at Lake Ranau Natural Tourism. The research employs purposive sampling with 392 respondents and is analyzed using Structural Equation Modeling (SEM) with Smart PLS 4.0 software. The findings indicate that memorable tourism experiences have a direct effect on satisfaction but not on loyalty. Destination image directly influences both satisfaction and loyalty, while tourist attractions directly affect satisfaction but not loyalty. Data was collected through questionnaires distributed to respondents. The results suggest that tourism managers can enhance visits and increase loyalty by focusing on these factors.